Magic steps - Pierce, Tamora (New York Scholastic Press, 2000)
When drawn into the investigation of murders perpetrated on a powerful family in Summersea, Sandy and her student Pasco undertake the dangerous mission of entrapping the invisible killers.
Keywords: Magic -- Fiction; Fantasy